Structural Modification of La[2]O[3]-TiO[2]-B Mixture After Mechanical Activation; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Dolmatov O. Yu. Oleg Yurevich; Zakusilov V. V. Vladislav Vladimirovich; Kuznetsov M. S. Mikhail Sergeyevich; Semenov A. O. Andrey Olegovich (2016, 2016)
Title screen